AKOMODASI KOMUNIKASI ANTAR BUDAYA PADA MASYARAKAT PENDATANG DENGAN MASYARAKAT LOKAL (Studi Pada Suku Minang Terhadap Suku Melayu lokal di Kelurahan Teluk Merbau Kec. Kubu Kabupaten Rokan Hilir) - Rinaldi, Ricki Eka; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia is a nation consisting of various ethnicities, races and cultures spread across various islands throughout the archipelago. This ethnic and cultural diversity makes the Indonesian nation rich in culture. With this diversity background, Indonesia will tend to become a nation that is open to immigrants and change. Where the majority of the population is inhabited by indigenous tribes, namely the Malay tribe. Apart from that, Teluk Merbau Village also has a pendang community, namely the Minang tribe. This research aims to determine the strategy of convergence, divergence and excessive accommodation between Minang and Malay ethnic cultures in Teluk Merbau Village, Kubu District, Rokan Hilir Regency. This research is a type of qualitative descriptive research that focuses on communication accommodation. This research was obtained through observation, in-depth interviews and documentation with 7 informants selected using purposive techniques with the criteria of having lived for 5 years, and being 23 years old and willing to be informants in this research. Where four informants are from the Minanag tribe and 3 informants are from the Malay tribe. The analysis technique used follows the concept given by Miles and Huberman. The results of this research show that the convergence strategy used by the Minang ethnic community and the Malay ethnic community in Teluk Merbau Village is adopting the language of the interlocutor, making body movements that indicate interest, adapting the speaking style and not limiting the distance between the interlocutor. The divergence strategy used is making no effort to know and use the other person's language, not using gestures that show interest when communicating, using one's own cultural speaking style, and showing ethnic differences when communicating. The causes of giving the label excessive accommodation are errors in using the language of the interlocutor, excessively assessing the culture of the interlocutor in relation to stereotypes, and maintaining distance when communicating. Keywords: Intercultural Communication, Communication Accommodation, Minang Tribe and Malay Tribe.